2015
DOI: 10.1016/j.jstrokecerebrovasdis.2015.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Dissecting Aneurysms of the Posterior Inferior Cerebellar Artery and Predictors of Outcome

Abstract: Endovascular treatment of isolated dissecting aneurysm of PICA had excellent clinical outcomes, hypertension, coexisting hydrocephalus, and time to operation (latter than 2 weeks), which were associated with unfavorable outcome. Long-term follow-ups are necessary to provide stronger conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
1
5
0
3
Order By: Relevance
“…Or results are almost matching with the published endovascular studies by Jin et al [17], Mohammadian et al [6], Li et al [18] and Debette et al [1]. In contrast to the endovascular outcome; Kitanaka et al reported that the long-term outcome of surgically treated lesions was somehow favorable, but there was a very high rate of postoperative neurological complications, and the major causes of disability were attributable to lower cranial nerve palsy and associated events in half of the patients with poor outcome [19].…”
Section: Discussionsupporting
confidence: 90%
“…Or results are almost matching with the published endovascular studies by Jin et al [17], Mohammadian et al [6], Li et al [18] and Debette et al [1]. In contrast to the endovascular outcome; Kitanaka et al reported that the long-term outcome of surgically treated lesions was somehow favorable, but there was a very high rate of postoperative neurological complications, and the major causes of disability were attributable to lower cranial nerve palsy and associated events in half of the patients with poor outcome [19].…”
Section: Discussionsupporting
confidence: 90%
“…Fujimura et al reported a case of fatal rebleeding after selective embolization of dissecting PICA aneurysms [22] while PAO is reported to have no recurrence or lower rate of recurrence. [14,23,11,21] Those 9 patients in our institution that took repeated DSA examination at 1 year after the operation showed no recurrence. The number of these cases was so limited that the recurrence rate of aneurysms cannot be reflected well.…”
Section: Discussionmentioning
confidence: 97%
“…Li et al reported 4 such cases with good clinical outcome. [14] In this research, we classified the tonsillomedullary segment into distal segment. 4 of 8 patients with aneurysms located in tonsillomedullary segment were managed with PAO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have tried to study the risk factors for recanalization. The aneurysm size, morphologies, treatment strategies, and hemodynamics have been found to be associated recanalization (4)(5)(6)(7)(8)(9). Some studies have tried to develop the models or grading scales to predict treatment outcome (4,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%